2022
DOI: 10.1177/03000605221081632
|View full text |Cite
|
Sign up to set email alerts
|

Association of the methylenetetrahydrofolate reductase (MTHFR) gene variant C677T with serum homocysteine levels and the severity of ischaemic stroke: a case–control study in the southwest of China

Abstract: Objective To determine whether the methylenetetrahydrofolate reductase ( MTHFR) C677T gene polymorphism is linked to the risk of ischaemic stroke and circulating homocysteine (Hcy) levels in a Chinese population. Methods This case–control study recruited angiogram-diagnosed patients with ischaemic stroke and healthy control subjects. The plasma Hcy concentrations were measured and the MTHFR C677T gene polymorphism was genotyped. The National Institutes of Health Stroke Scale (NIHSS) was used to assess the seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
4
0
2
Order By: Relevance
“…Los niveles circulatorios elevados de homocisteína han sido reconocidos como un factor de riesgo independiente para enfermedad cardiovascular y particularmente se relaciona con la extensión de la isquemia en ACV (2), donde los mecanismos fisiopatológicos incluyen alteraciones en el endotelio, estrés oxidativo y la inflamación con activación de la coagulación (20). Además, induce la hipometilación del ácido desoxirribonucleico y empeora la apoptosis, promoviendo la susceptibilidad al daño neuronal (9,(21)(22).…”
Section: Discussionunclassified
“…Los niveles circulatorios elevados de homocisteína han sido reconocidos como un factor de riesgo independiente para enfermedad cardiovascular y particularmente se relaciona con la extensión de la isquemia en ACV (2), donde los mecanismos fisiopatológicos incluyen alteraciones en el endotelio, estrés oxidativo y la inflamación con activación de la coagulación (20). Además, induce la hipometilación del ácido desoxirribonucleico y empeora la apoptosis, promoviendo la susceptibilidad al daño neuronal (9,(21)(22).…”
Section: Discussionunclassified
“…Age Numerous studies have shown that various environmental variables and genetic variations contribute to the etiology of CI (19). Previously published studies have demonstrated associations between MTHFR polymorphisms and CI, although the results have been mixed (20,21).…”
Section: Genotype Nmentioning
confidence: 99%
“…Many researchers have examined the relationship between MTHFR rs1801133 (677C>T) polymorphism and IS risk. However, there have been no definitive conclusions because different populations were examined and inconsistent results were obtained ( Herak et al, 2017 ; Jiménez-González et al, 2021 ; Huang et al, 2022 ). Two meta-analyses were performed separately in 2016 and 2019 that reported a correlation between MTHFR rs1801133 (677C>T) polymorphism and IS ( Song et al, 2016 ; Chang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%